Focus on advanced English C.A.E: Grammar practice (Edinburgh Gate, Halow, 1997)
This book provides extra practice to support the main grammar and vocabulary areas found in each of the 14 units of Focus on Advanced English C.A.E. It also contains: extra practice in CAE writing skills, four Progress Tests; study tips to help with common grammatical problems; space for written answers.
Keywords: english language - examinations - study guides,english language - textbooks for foreign speakers,test of english as a foreign language - study guides